The invention of a market: The political economy of biometric voting in Africa - (:unkn) unknown (My University, 2023)
Biometric voting developed in Africa during the 2000s. The technology is now used for voter identification in over half of African countries. Our research aims to make sense of the invention of this market. The study is based on the combination of two methodologies. On the one hand, we compiled a database of the election technologies used in each African country and of the companies that sold them. On the other hand, we engaged in qualitative research, including interviews and ethnographic observations. We show that the biometric voting market has been shaped not only by corporate interests. The market is also influenced by normative ideas as well as by the knowledge and know-how of actors with diverse backgrounds: donors, democracy professionals, and African political personnel. By adopting a political economy approach, we show how this market is embedded in postcolonial logics, and ultimately bring to light the enduring legacies of the former French empire.
Keywords: African Research